A Structural and Functional Perspective of Death Receptor 6 - Ren, Xiuying; Lin, Zhi; Yuan, Wensu (Frontiers in Pharmacology, 2022)
As a member of the tumor necrosis factor receptor superfamily (TNFRSF), death receptor 6 (DR6) has a similar structural architecture to other family members. The extracellular region of DR6 contains four cysteine-rich domains, followed by a single-pass transmembrane domain and an intracellular region. Since its discovery, DR6 has become an orphan receptor ubiquitously expressed to transduce unique signaling pathways. Although the free ectodomains of β-amyloid precursor protein (APP) can bind to DR6 to induce apoptotic signals, the natural ligands of DR6 still remain largely unknown. In this review, we focus on recent research progress of structural and functional studies on DR6 for better understanding DR6-mediated signaling and the treatment of DR6-related diseases.